2D networks of metallo-capsules and other coordination polymers from a hexapodal ligand12. Issue 28 (26th June 2018) - Thorp-Greenwood, Flora L.; Berry, Gilberte Therese; Boyadjieva, Sophia S.; Oldknow, Samuel; Hardie, Michaele J.
Abstract : 2D M3 L2 coordination polymers (M = Re(i ), Cu(ii ), Co(ii ), Ni(ii )) feature metal-linked M6 L2 -cages, and the Re(i ) material absorbs iodine. Abstract : The hexapodal ligand hexakis(isonicotinoyl)cyclotricatechylene (L1) belonging to the cyclotriveratrylene family of host-molecules has been synthesised and used in the assembly of a series of coordination polymer materials with Re(i ), Co(ii ), Cu(ii ), Ni(ii ) and Ag(i ) salts. Single crystal structures of the coordination polymers [Re3 (L1)2 Br3 (CO)3 ]1, and an isomorphic [M3 L2 ] series where M = Co, Cu or Ni, reveal 2D framework structures with a simplified topology of 3 6 orhxl . These are composed of M6 (L1)2 metallo-cages linked together in a pair-wise fashion through each metal centre. Compound1 is a rare example of a rhenium coordination polymer and was investigated for guest uptake from solution, complexing I2 . The mixed-ligand species [Cu2 (L1)(CF3 CO2 )3 (isonicotinate)] forms a (3, 4, 5)-connected 2D coordination polymer, while [Ag2 (L1)(DMF)2 ]·2BF4 ·2(H2 O)·6(DMF) features a 2D network of (3, 6)-connectivity and with kagome dual (kgd ) topology.